2014
DOI: 10.1016/j.oceaneng.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of a fleet of towed AUVs

Abstract: This paper investigates the influence of the propeller on the drag of twin self-propelled AUVs, firstly, to examine the fleet performance for various propulsive conditions of leading and following AUV and, secondly, to study the parametric influence of transverse separations and longitudinal offsets on the fleet's drag. A series of CFD RANS-SST simulations have been performed at the Reynolds Number 3.2 × 10 6 with a commercial code ANSYS CFX 12.1. Mesh convergence is tested and validated with experimental and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…As the transverse separation increases up to 0.37L, the increase in accelerated flow due to the action of propeller reduces, resulting in no propeller race deduction. These results and the previous towed studies (Rattanasiri et al, 2014) suggested that the distance of 0.5L is required as the minimum transverse separation to exclude body-tobody interaction and the propeller race deduction.…”
Section: Parallel Regionsupporting
confidence: 77%
See 3 more Smart Citations
“…As the transverse separation increases up to 0.37L, the increase in accelerated flow due to the action of propeller reduces, resulting in no propeller race deduction. These results and the previous towed studies (Rattanasiri et al, 2014) suggested that the distance of 0.5L is required as the minimum transverse separation to exclude body-tobody interaction and the propeller race deduction.…”
Section: Parallel Regionsupporting
confidence: 77%
“…The computational cost of using the medium mesh (8.9 million elements) is 10 times lower then that of the fine mesh (22.7 million elements) with a less than 2% variation in drag. Details of the fluid domain discretisation and mesh strategy's validation is completely presented in Rattanasiri et al (2014). Results utilising these meshes exhibited good correlation with the pressure distribution, the side-force coefficient, form factor and the towed drag measured in: the wind tunnel experiments (Molland and Utama, 1997), previous numerical analysis (Molland and Utama, 2002) and empirical predictions (Hoerner, 1965).…”
Section: Numerical Settings and Mesh Strategymentioning
confidence: 96%
See 2 more Smart Citations
“…Note added in proof The analyses carried out in the previous sections neglected viscosity effects. As mentioned above a recent study [37,38], which appeared while this paper was under initial review, examined, among others, the impact of spacing between slender bodies on the viscous drag. Following [37], we define C B;j ¼ C DðB;jÞ À C DðsÞ C DðsÞ ; for j ¼ 1; 2…”
Section: Summationmentioning
confidence: 99%